2005
DOI: 10.1177/154405910508400415
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Erosion Simulation by Cantilever Beam Fatigue and pH Change

Abstract: Exposed root surfaces frequently exhibit non-carious notches representing material loss by abrasion, erosion, and/or abfraction. Although a contribution from mechanical stress is often mentioned, no definitive proof exists of a cause-effect relationship. To address this, we examined dimensional changes in dentin subjected to cyclic fatigue in two different pH environments. Human dentin cantilever-beams were fatigued under load control in pH = 6 (n = 13) or pH = 7 (n = 13) buffer, with a load ratio (R = minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 12 publications
2
28
0
6
Order By: Relevance
“…Staninec et al 36 investigated the magnitude and location of tooth structure loss using sectioned segments of tooth structure that were subjected to cyclic mechanical loading. Despite the obvious limitation of using sectioned segments of tooth structure, they found that there was a greater loss of material in high-stress areas, supporting the possibility of abfraction.…”
Section: Experimental Evidence Of Abfractionmentioning
confidence: 99%
“…Staninec et al 36 investigated the magnitude and location of tooth structure loss using sectioned segments of tooth structure that were subjected to cyclic mechanical loading. Despite the obvious limitation of using sectioned segments of tooth structure, they found that there was a greater loss of material in high-stress areas, supporting the possibility of abfraction.…”
Section: Experimental Evidence Of Abfractionmentioning
confidence: 99%
“…An in vitro simulation demonstrated material loss from the dentin surface due to the presence of cyclic (fatigue) stresses, although the magnitude of the loss was small. [14] However, once a notch is formed, it does act to concentrate stress in that location and thus is presumed to be a factor in the eventual de-bonding failure of restorations of NCCL's. [15,16] The fatigue behavior of dentin has been examined in recent studies [17,18], but there are no corresponding studies on the fatigue properties of enamel.…”
Section: Introductionmentioning
confidence: 99%
“…The high clinical incidence and prevalence of noncarious cervical lesion (NCCL) has led to questions about the factors involved on the formation and progression of these lesions [1][2][3][4][5][6][7][8]. Clinically, the association among maxillary premolars with endodontic access, MOD restoration, and NCCL presence is a routine situation in clinical practice.…”
Section: Introductionmentioning
confidence: 99%